On the Sufficient Conditions for the Solubility of Algebraic Inverse Eigenvalue Problems (Journal of Computational Mathematics, 1992)
With the help of Brouwer's fixed point theorem and the relations of the eigenvalues and diagonal elements of a Hermitian matrix, we give some new sufficient conditions for the solubility of algebraic inverse eigenvalue problems.